A Clinical Study on Canine Pyometra - Verma, Atul Kumar; Saroha, Harshit; Srivastava, Aman; Shambhavi,; Patel, Akhil; Tripathi, Ashutosh; Shukla, Manish Kumar; Singh, Vijay (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Pyometra is an important gynaecological disorder of canine females along with dystocia and transmissible venereal tumor. Canine pyometra is problematic for canine owner and sometimes fatal in canines in severe cases. So, this study was aimed to know the incidence of pyometra among different gynaecological disorders, breed-wise, and factors affecting incidence of pyometra. A total 178 female dogs, presented with gynaecological disorders at VCC, Meerut, were included in this clinical study. Maximum incidence of canine pyometra was observed in five to six years age group. The incidence was found more in nulliparous (intact) animals and in Labrador breed. Incidence of open cervix pyometra was more common than closed cervix pyometra. USG can be used as a tool for the diagnosis of closed cervix pyometra. Mifipristone, Cabergoline, Misoprostol/Dinoprostone (oral/vaginal prostaglandin) along with antibiotic and other supportive therapy was found very effective in canine pyometra.
Keywords: Mifepristone; Nulliparous; Pyometra; Cabergolin; Canine